Esterification of renewable levulinic acid to ethyl levulinate biodiesel catalyzed by highly active and reusable desilicated H-ZSM-5 - Nandiwale, Kakasaheb Y.; Niphadkar, Prashant S.; Deshpande, Shilpa S.; Bokade, Vijay V. (Journal of Chemical Technology and Biotechnology, 2014)
BACKGROUNDIn the near future, fossil fuel will have limitations in terms of availability and also great concerns over its environmental impact. New routes and related technologies based on renewable feedstocks can overcome most of these problems associated with fossil fuel. Among current biodiesel sources, ethyl levulinate (EL) biodiesel obtained from catalytic esterification of renewable levulinic acid (LA) with ethanol has received a great deal of attention. The use of desilicated H-ZSM-5 (DH-ZSM-5) as heterogeneous acid catalyst for EL biodiesel production in a closed system (under autogeneous pressure) was studied. RESULTSThe effect of reaction parameters such as ethanol to LA molar ratio (4:1 to 10:1), catalyst to LA ratio (0.10-0.25), speed of agitation (100-400rpm), particle size (53-355 mu m), reaction temperature (363-403K) and reaction time (7h) was investigated to maximize LA conversion. CONCLUSIONLevulinic acid conversion reached 95% over DH-ZSM-5 and the catalyst was reusable for up to six cycles. This LA conversion and the catalyst reusability values are higher than others reported in the literature. A pseudo-homogeneous (P-H) kinetic model indicated that reaction rate constants increased with increasing molar ratio, catalyst to LA ratio and reaction temperature. The activation energy decreased from 73.14 to 21.08 kJ mol(-1) when increasing the catalyst to LA ratio from 0.10 to 0.25, which implies a kinetically controlled reaction. (c) 2013 Society of Chemical Industry
Keywords: desilicated H-ZSM-5; Esterification; ethyl levulinate; levulinic acid